Pembuatan Aplikasi Perhitungan Harga Pokok Produksi di PT. Arcon Perdana Globalindo - Tedjokumolo, Frederick Alexander; Adipranata, Rudy; Rostianingsih, Silvia (Jurnal Infra, 2015)
PT. Arcon Perdana Globalindo is a furniture manufacturing company. The company will produce furnitures according to customerâs requests. Custom orders mean different selling price for every order. Fluctuative price and diversity of materials as well as the cost elements are the main issues that the company has to face.Â  With that problem as a background, the author create a system to calculate production cost that can address the problem mentioned. The author create the application based on web using PHP and HTML5 as the core programming language, Bootstrap front-end framework and PostgreSQL database. Costing method used are average costing and job order costing. The application is designed to memorize each productâs Bill of Material, schedule a production and accomodating inventory control besides calculating COGM cost. The result of applicationâs examination showed that the calculation results are accurate within production elements scope. However it requires an extensive usage to be able to effectively cover calculation of selling price. For further development, an accounting information system could be added.